Dendritic cell vaccines for cancer therapy: Fundamentals and clinical trials - Romagnoli, Graziela Gorete [UNESP]; Kaneno, Ramon [UNESP] (Springer Nature, 2020)
Since conventional chemo- and radiotherapy and surgery are not completely satisfactory to fight cancer, active and passive immunotherapeutic approaches have figured as effective agents of customized medicine. Dendritic cells (DCs) are key cells to trigger an effective antitumor response, being the only antigen-presenting cells (APCs) able to prime naïve T lymphocytes for tumor antigens. Therefore, several approaches have been proposed to use these cells as therapeutic antitumor vaccines. Different strategies of tumor antigen delivery, as well as the use of the best DC activators, are in constant search for the development of more immunogenic DC-based vaccines. In the present chapter, we reviewed the strategies for developing clinical-grade DC vaccines and the data of clinical trials with patients with selected types of cancer. Current studies show positive but not definitive results, indicating that the association with other immunotherapeutic agents, such as checkpoint blockers, or even chemotherapeutic agents may contribute to achieve the clinical regression of cancer.
Keywords: Antitumor immunity; Cancer; Dendritic cell vaccines; Immunomodulation; Immunotherapy